Psikoedukasi: Konflik Peran Ganda vs Kepuasan Pernikahan: Pentingnya Regulasi Emosi bagi Pasangan Muda - Analisa Imara; Roswiyani Roswiyani; Monty P. Satiadarma (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Young married couples in Jakarta often face challenges in balancing work and family demands, which can lead to role conflict. This conflict contributes to decreased marital satisfaction, especially when individuals have low emotional regulation. This community service (PKM) activity aims to provide psychoeducation on role conflict, marital satisfaction, and emotional regulation strategies to young employees of PT Treasure Citrarasa Indonesia through an online seminar. The activity was conducted in three stages: pre-test, presentation of material, and interactive discussion. The results of the activity showed an increase in participants' understanding of role conflict and emotional regulation strategies, as well as a greater awareness of the importance of adaptive communication in marital relationships. Additionally, participants gained new insights into how effective emotional regulation can reduce stress and improve marital satisfaction. Thus, this psychoeducation activity has the potential to be an effective intervention in enhancing relational well-being for young couples, particularly in managing role conflict amidst work and family demands. The activity also highlights the importance of understanding and applying emotional regulation strategies in daily life to maintain marital harmony.